Recurrent summer drought temporarily stimulates fine root growth but enhances winter root losses in alpine grassland - Möhl, Patrick; Hiltbrunner, Erika (Frontiers in Plant Science, 2025)
By the end of the 21st century, frequent droughts and substantial shifts in snowmelt are expected to massively impact the biomass production of alpine grasslands. While the biomass of alpine plants consists to >80% of roots, little is known about the root growth dynamics in these ecosystems. To fill this gap, we capitalized on a longer-term experiment in the Swiss Alps with annually recurring treatments imposing advanced and delayed snowmelt and summer drought lasting 5 and 10 weeks. Over 3–4 growing seasons (2019–2022), we weekly quantified total root length of the plant community at two different soil depths (0–10 cm and 10–20 cm) using 90 minirhizotrons in 45 plots. We jointly assessed leaf elongation (of six abundant plant species) as proxies for the dynamics of biomass production. Increases in root length during summer continued beyond canopy development, with the duration of net root growth roughly double that of leaf expansion. Earlier and later snowmelt did not affect the proxies for total growth of leaves or roots but simply shifted their growing phases. Drought reduced leaf elongation across plant species whereas root length was stimulated by the 5-wk (not the 10-wk) drought in two seasons (+19% on average, 2020–2021). Natural rewetting after drought increased root growth by 38–77% compared to controls, but only in the 2020 growing season. Total root length in the topsoil declined by 7–15% during the last two winters, amounting to about one fourth of the previous seasons’ increase in root length. These root losses were 1.5 times higher following the 10-wk drought treatment. Our results highlight that earlier snowmelt alone will not stimulate productivity in alpine grassland. Root growth responses to drought depend on its duration and the long winter periods contribute to root losses, particularly in combination with severe drought in the preceding growing season.